Platelets, inflammation and anti-inflammatory effects of antiplatelet drugs in ACS and CAD - Müller, Karin A L; Chatterjee, Madhumita; Rath, Dominik; Geisler, Tobias (Thrombosis and haemostasis, 2015)
Platelets play a pivotal role in chronic inflammation leading to progression of atherosclerosis and acute coronary events. Recent discoveries on novel mechanisms and platelet-dependent inflammatory targets underpin the role of platelets to maintain a chronic inflammatory condition in cardiovascular disease. There is strong and clinically relevant crosslink between chronic inflammation and platelet activation. Antiplatelet therapy is a cornerstone in the prevention and treatment of acute cardiovascular events. The benefit of antiplatelet agents has mainly been attributed to their direct anti-aggregatory impact. Some anti-inflammatory off-target effects have also been described. However, it is unclear whether these effects are secondary due to inhibition of platelet activation or are caused by direct distinct mechanisms interfering with inflammatory pathways. This article will highlight novel platelet associated targets that contribute to inflammation in cardiovascular disease and elucidate mechanisms by which currently available antiplatelet agents evolve anti-inflammatory capacities, in particular by carving out the differential mechanisms directly or indirectly affecting platelet mediated inflammation. It will further illustrate the prognostic impact of antiplatelet therapies by reducing inflammatory marker release in recent cardiovascular trials.